POST-TRUTH, MEDIA SOSIAL, DAN MISINFORMASI: PERGOLAKAN WACANA POLITIK PEMILIHAN PRESIDEN INDONESIA TAHUN 2019 - MOCHAMAD IQBAL JATMIKO (Jurnal Dakwah Tabligh, 2019)
Today, positivistic in the political sphere has been invaded by the notion of relativism. The post-truth regime bursts into political discourse and public awareness. Community opinion is driven in distrust of objective data. Reality manipulation is increasingly being carried out for political purposes. In this condition, the community is more secure with pseudo-facts that match personal beliefs. The discourse of political lies is then packaged into alternative discourses to match objective facts. The development of massive information technology, through online media, helps the distribution of discourse in the community. Public awareness through opinion is built and new facts are created. This is how Indonesian political contestation in 2019 is full of strange discourses without data. Political recitals are chaotic because of the disparity among factions that spread lies, hatred, and nonsense. Community elements are exploited for the sake of discourse battle victory. Like passive objects that are annihilated, people are made slaves to win the political elite.